Factors Linking Declining Reef Health Ecosystem to Poverty in Lagonoy Gulf, Eastern Bicol, Philippines - Mendoza, Jr. , Antonino B.; Nieves, Plutomeo M.; Borejon, Michael C. (Journal of Social Science Studies, 2021)
This paper provided likely linkage between poverty and reef health status in Lagonoy Gulf. It showed that fishers are poor as reflected by their weekly income ranging from PhP 2,500.00 to <500.00 averaging PhP 1,214.00 which is way below the PhP 3,596 week-1 poverty threshold for Bicol Region. Population density in coastal municipalities is highest in Albay with 512 ind. km-2 and least in Catanduanes with 325 ind. km-2. Fishers are relatively ageing with mean age of 48 years and average fishing experience of 29 years. Majority only reached or finished primary level, and only 6% reached college. Five out of six do not own boat and gears, showing financial incapacity. Hook and lines were used by 66% of the fishers while, nets comprised 32%. Living coral cover declined from 1993 to 2018 by almost 25%. High dependence to coastal resources, high demand for seafood, destructive gears, lack of supplemental sources of income, low educational background, lack of skills, low income are identified contributory factors to habitat degradation. With the declining reef health and fish catch, fishers that are living below poverty threshold are more likely to become poorer because the reef’s capacity to provide goods and services is lost.